Study on Incidence and Progression of Refractive Errors in Medical Students - Bussa, Manjula; Ravi, Babu G; Nehakamalini, P (Nepalese Journal of Ophthalmology, 2019)
Purpose: To study the incidence and progression of refractive errors in medical students.Methods: This is a retrospective study including 200 medical students of our college during the period of July 2015 to June 2018. Examination included visual acuity testing using Snellens chart, slit lamp biomicroscopy, fund us examination with direct ophthalmoscope, indirect ophthalmoscope and refraction. Students were examined for refractive errors and findings compared with pre-admission data. Changes in spherical, cylindrical power analysed.Results: Prevalence of Myopia increased from 40% to 48%. Incidence of new refractive errors in emmetropes was 8%. Myopic change found was -0.75D to -1.0D.Conclusion: Students in medical colleges have high prevalence of myopia, high incidence of adult onset myopia and statistically significant progression. Parental history, prolonged eye strain, excessive use of electronic gadgets, decreased outdoor activity and urban background had significant association with prevalence of myopia.